Psychometric Properties of Parenting Measures in Indonesia - Riany, Yulina y.riany@uq.edu.au; Cuskelly, Monica; Meredith, Pamela (UI Scholars Hub, 2018)
We examined the psychometric properties of two parenting measures, the Parenting Styles and Dimensions Questionnaire (PSDQ) and the Parent-Child Relationships Questionnaire (PCRQ) which were translated into Indonesian for use in Indonesia. The Indonesian versions of these questionnaires were completed by 514 parents and 459 parents, respectively. Participants were parents (mostly mothers) of typically developing children, who completed the measures through an online or paper-based survey. Exploratory Factor Analysis (EFA), parallel analyses,internal and external construct validity,and internal reliability were performed on both measures. Results revealed that the translated version of the PSDQ consisted of three factors. Two of these factors reflected the Authoritative and Authoritarian subscales of the original measure; however, the Permissive subscale was not obtained. A third factor, labelled Reasoning, was extracted. The translated PCRQ was found to have the same structure as the original version of the measure. Some modifications were required for both instruments, and the modified versions of the instruments had acceptable internal consistency. Development of these translated and modified instruments will support parenting research within Indonesia.